2015
DOI: 10.1159/000381511
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis of Endogenous Anticholinergic Activity in Alzheimer's Disease

Abstract: In this article, we review and repropose our hypothesis of the endogenous appearance of anticholinergic activity (AA) in Alzheimer's disease (AD). First, we introduce our previous articles and speculate that, because acetylcholine (ACh) regulates both cognitive function and inflammation, downregulation of this neurotransmitter causes upregulation of the inflammatory system. AA then appears endogenously with the production of cytokines and the downregulation of ACh in AD. To support our hypothesis, we present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…, for example, found that a long‐term blockade of the muscarinic receptors, as an effect of anticholinergic drugs, increases the presence of amyloid‐β peptide in the cortex, hippocampus and amygdala. Consequently, since Alzheimer’s Disease reflects lower cholinergic activity, the use of anticholinergic drugs with central action might affect cognitive performance .…”
Section: Discussionmentioning
confidence: 99%
“…, for example, found that a long‐term blockade of the muscarinic receptors, as an effect of anticholinergic drugs, increases the presence of amyloid‐β peptide in the cortex, hippocampus and amygdala. Consequently, since Alzheimer’s Disease reflects lower cholinergic activity, the use of anticholinergic drugs with central action might affect cognitive performance .…”
Section: Discussionmentioning
confidence: 99%
“…AD is a neurodegenerative disease characterized by a progressive loss of learning and memory as well as neuronal death. The hippocampus, the main brain region involved in memory processing, is influenced by cholinergic modulation [ 95 ]. One of the well characterized anomalies associated with neurotransmitter alterations is the degeneration of cholinergic neurons in the nucleus basalis of Meynert and the loss of cholinergic inputs to the neocortex and hippocampus.…”
Section: The Cholinergic Hypothesismentioning
confidence: 99%
“…Based on this speculation, we propose "the hypothesis of endogenous appearance of AA in AD" [6]. That is, when the downregulation of ACh reaches critical level, AA appears endogenously by way of hyperactivation of inflammatory system and accelerates amyloid pathology [5,6].…”
Section: Opinionmentioning
confidence: 99%
“…Based on this speculation, we propose "the hypothesis of endogenous appearance of AA in AD" [6]. That is, when the downregulation of ACh reaches critical level, AA appears endogenously by way of hyperactivation of inflammatory system and accelerates amyloid pathology [5,6]. Because the factors those cause AA and now reported three other than downregulation of ACh, i.e., medication [7], physical illness [8] and mental stress [9].…”
Section: Opinionmentioning
confidence: 99%